2010
DOI: 10.1590/s0103-90162010000200018
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation in tropical ecological restoration

Abstract: Ecological theories of facilitation and nucleation are proposed as a basis for environmental restoration in tropical ecosystems. The main goal of this paper is to present restoration techniques based on the concept of nucleation, in which small nuclei of vegetation are established within a degraded land. The nucleation techniques (artificial shelters for animals, planting of herbaceous shrub life forms, soil and seed bank translocation, seed rain translocation, soil and seed rain translocation's seedling set, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
38

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 55 publications
(57 reference statements)
1
77
0
38
Order By: Relevance
“…Whereas a number of authors have suggested that habitat heterogeneity should be higher with a tree island planting approach (Rey Benayas et al 2008;Reis et al 2010;Corbin and Holl 2012), we know of no other studies that have directly compared this approach to more homogeneous restoration strategies. Past studies, however, have shown that other restoration strategies that are applied in a patchy manner (e.g., Baer et al 2004-fertilization and soil depth; Gundale et al 2006-forest thinning) can successfully restore small-scale nutrient heterogeneity.…”
Section: Resource Heterogeneitymentioning
confidence: 98%
See 2 more Smart Citations
“…Whereas a number of authors have suggested that habitat heterogeneity should be higher with a tree island planting approach (Rey Benayas et al 2008;Reis et al 2010;Corbin and Holl 2012), we know of no other studies that have directly compared this approach to more homogeneous restoration strategies. Past studies, however, have shown that other restoration strategies that are applied in a patchy manner (e.g., Baer et al 2004-fertilization and soil depth; Gundale et al 2006-forest thinning) can successfully restore small-scale nutrient heterogeneity.…”
Section: Resource Heterogeneitymentioning
confidence: 98%
“…These tree islands facilitate natural recovery processes in degraded landscapes, as they slowly expand, through growth of planted seedlings and increased dispersal and establishment of new seedlings, and may ultimately coalesce (Rey Benayas et al 2008). The method attempts to simulate nucleation processes that naturally occur in successional forest and may leave less of a legacy of planted trees (Yarranton and Morrison 1974;Reis et al 2010). Indeed, our past research in the neotropics indicates that planted tree islands serve to attract and provide habitat for animals, which encourages zoochorous seed dispersal and seedling establishment (Zahawi and Augspurger 2006;Cole et al 2010;Zahawi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon completion of their reproductive cycle, annual plants die, thereby giving room to other species (Reis et al 2010). Therefore, the fast emergence of annual species can favor the entire postflood succession (Lortie & Turkington 2008).…”
Section: Temporal Variationmentioning
confidence: 99%
“…Nucleation is understood as the capacity of species to provide significant improvement in environmental quality, increasing the probability of occupation of this environment by other species (Yarranton and Morrison, 1974;Reis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%